Contexto familiar de crianças com síndrome de Down: interação e envolvimento paterno e materno - Silva, Nancy Capretz Batista da (2007)
Changes in society bring a new way of familiar organization and a new look at the participation of the man in this context. Although the father s importance has been recognized, on Brazil, there are few studies which aim at knowing the relation between the father and his child with special needs characteristics. Besides, the findings about the fathers involvement with their children are varied: sometimes mothers are more involved, others fathers spend a significant time with their special needs children. A better characterization would be obtained with observation measures as much father-child interaction, as mother-child interaction, searching in this manner a systematic vision of the family. In this way, the objective of the present study was to describe the interactions of father and mother with their children with Down Syndrome in play situation and compare these interactions, taking in account variables such as stress, empowerment, self-esteem, home environment and additionally the father s participation on the child s care and home activities, the influence of the grandparents and the paternal vision under aspects of fatherhood and the child s deficiency. Ten families having children with Down Syndrome aging between two and six years took part on this study; from diverse socioeconomic and educational status; residents in Ribeirão Preto and São Carlos cities. It had been used: Critério Brasil, Questionário de Caracterização do Sistema Familiar, Guia Geral de Transcrição dos Dados de Entrevista, Entrevista de Caracterização do Papel do Pai Brasileiro na Educação da Criança com Deficiência Mental, Inventário HOME, QRS-F, ISSL, FES, PSOC, Protocolo de Categorias de Análise das Filmagens de Interação and Sistema Definitivo de Categorias Observacionais. These tools were the base for the interviews, home observation and interaction of the family members filming analysis (in the total of one hour). The results indicate that: the mother was the main responsible for the home activities; the father shared the child s care in half of the sample; the social web of support was composed by the own family and relatives; great part of the grandparents participated of the familiar life; only a family offered a rich environment in stimulation and support for the child; the genitors showed low percentages of stress related to the presence of the deficient child; half of the parents presented indicative symptoms of stress; all considered theirselves empowered; and the majority exhibited elevated self-esteem. In relation to the fathers: half of them passed good part of the day with their children; the majority considered theirselves a good father; all considered theirselves an important figure on his children lives; and most of them believed that the child would have a life pretty close to the normal in the future. In relation to the observations, olhar na direção da criança (looking to the child s direction) was the positive behavior of greater frequency for the parents; none of the genitors corrected inappropriate behaviors; and the negative behavior of higher frequency was comentários negativos (negative commentaries). The most emmited positive behavior by children was prestar atenção (pay attention) and the negative behavior was desobediência (disobedience). Furthermore, the most frequent kind of activity was Brincadeiras com objetos (Play with objects) and the interactions occured mainly at Conjunta (Joint) way, with Direta (Direct) transition from one activity to another, with Sincronia (Synchrony), Supervisão (Supervision), Amistosidade (Friendly) and Liderança (Leadership). These fathers, on general, seems to be involved with their children, offering varied stimulation for them, and present low level of stress and show themselves empowered in relation to the presence of a deficient child.